Design and Chemical Engineering of Polymeric Biomaterials: Functionalization, Crosslinking, and Characterization Strategies for Advanced 3D Bioprinting - Khan Jani, Fatemeh (Biocompounds, 2025)
Three-Dimensional (3D) bioprinting of polymeric biomaterials has emerged as a transformative platform in tissue engineering, enabling the fabrication of patient-specific scaffolds with precise spatial control. The performance of these constructs is fundamentally governed by the chemical architecture of the constituent polymers and the mechanisms of crosslinking that dictate their rheological behavior, mechanical integrity, and degradation kinetics, which collectively determine print fidelity and biological functionality. This review synthesizes current advances in natural and chemically modified synthetic polymers, elucidates the physicochemical principles underlying physical, ionic, and covalent crosslinking modalities, and highlights the intricate structure-property relationships that shape the behavior of printable bioinks. Moreover, contemporary characterization methodologies, recent material innovations, persistent challenges, and emerging directions aimed at enhancing biocompatibility and functional maturation are critically examined. Collectively, this work provides a rigorous framework to guide the rational design, optimization, and translational development of polymer-based biomaterials for next-generation regenerative medicine.